Yogyakarta Hijabers’ Consumer Behavior In Shopping Hijab On Online Media - Frizki Yulianti Nurnisya, Frizki Yulianti Nurnisya (2015)
Indonesia is a country having the largest Muslim population in the world. In Islamic teaching, Muslim women’s head is one of their private body parts that they oblige to cover it by wearing veil, well known as hijab. Clothes of Muslim women were assumed and looked old-fashioned, yet hijabers considered as an icon of stylish, modern, chic, and modest Muslim women emerge and alter perception on Islamic clothing. The high-class fashion designs propose a new social class that is more exclusive for women to cover their private parts.